2011
DOI: 10.1592/phco.31.7.695
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of U‐500 Insulin Therapy in Patients with Insulin‐Resistant Type 2 Diabetes Mellitus

Abstract: In patients with insulin-resistant diabetes who have requirements of more than 200 units/day or 100 units/injection, use of U-500 regular insulin provided the same or better glucose control compared with U-100 insulin, with fewer daily injections and reduced injection volume. Although this drug represents an excellent treatment option, its safe use requires an experienced physician, a motivated and cooperative patient, and a dynamic diabetes management team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 25 publications
1
33
2
Order By: Relevance
“…25 Two studies reported that the number of insulin injections significantly decreased. 25,26 In addition, there…”
Section: Use Of U-500r Via Multiple Daily Injectionsmentioning
confidence: 99%
“…25 Two studies reported that the number of insulin injections significantly decreased. 25,26 In addition, there…”
Section: Use Of U-500r Via Multiple Daily Injectionsmentioning
confidence: 99%
“…1,2 In selected patients, U-500 regular insulin (U500) allows for administration of high TDD at volumes lower than that required with standard U-100 insulin (U100) preparations. 3 This higher insulin concentration alters the pharmacokinetic properties of regular insulin to that of an intermediate-or long-acting insulin (LAI) preparation.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Standard recommendations for U500 suggest that it be administered in divided doses of two or three injections per day as the sole insulin preparation to meet both basal and meal-related insulin requirements. 2,3 Others have suggested that it be administered as a component of a basal/bolus insulin (BBI) regimen in combination with either rapid-acting insulin (RAI) or LAI preparations. [3][4][5][6][7] These suggestions result in uncertainty and variability among clinicians in how to optimally prescribe and implement U500.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, it creates a typical acute inflammatory reaction immediately, and within a few days macrophages engulf the pigment, migrate to the regional lymph nodes, and cause varying degrees of inflammatory reaction. 2,3 The presence of enlarged lymph nodes secondary to reaction to tattoo pigment recently has become significant in the malignant melanoma literature, where the presence of enlarged pigmented lymph nodes has led to the erroneous presumption of recurrence or metastasis. 4,5 Additionally, lymph node calcifications attributable to tattoo pigment have been mistaken for metastatic breast cancer on screening mammography.…”
Section: Casementioning
confidence: 99%
“…Typical insulin regimens for diabetic patients during pregnancy include combinations of intermediate-acting insulin and mealtime doses of short-acting insulin; however, for patients with increasingly high insulin requirements, these frequent, high-volume injections may lead to decreased insulin effect, compromised patient adherence, and inadequate glycemic control. 2 …”
mentioning
confidence: 99%